Excise Regulation For Single-Use Plastics As An Effort To Reduce Environmental Pollution In Indonesia - Maisyarani, Ghina; Istislam, Istislam; Indra Rahmawan, Triya (Universitas Negeri Gorontalo, 2025)
This study examines the legal vacuum in the regulation of excise duty on single-use plastics in Indonesia. The accumulation of poorly managed plastic waste has become a serious threat to the environment, but until now there has been no strong legal basis to deal with this problem. Although single-use plastics meet the criteria of excisable goods (BKC) as stipulated in Article 2 Paragraph (1) of Law No. 39 of 2007 on excise, until now it has not been regulated in excise regulations. Therefore, the imposition of excise duties is a strategic step in controlling the consumption of single-use plastics and reducing the impact of environmental pollution. This study uses normative juridical method with comparative approach to law and legislation approach. Legal material is collected through the study of literature and internet sources, then analyzed by prescriptive techniques as well as through systematic interpretation. The results show that the urgency of regulating excise duty for single-use plastics can be viewed from a philosophical, juridical, and sociological perspective. This regulation is in line with the values of Pancasila, the existing legal framework, and efforts to overcome environmental pollution in Indonesia. A comparative analysis of excise policy in Ireland and Denmark provides insight into applicable regulatory models. As a recommendation, This study proposes a draft clause in the excise law to support the expansion of the types of excisable goods, which is currently still under discussion.